1990
DOI: 10.1111/j.1348-0421.1990.tb01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cytotoxicity of Active Macrophages by Mycoplasma: Role of Mycoplasma‐Associated Induction of Tumor Necrosis Factor‐α (TNF‐α) in Macrophages

Abstract: Tumor necrosis factor-alpha (TNF-a)-inducing activity of several mycoplasmas including Mycoplasma pneumoniae, a causative agent in human respiratory infectious diseases, was investigated. Purified peritoneal macrophages from BALB/c mice markedly enhanced their cytotoxic activity to Meth A cells, when cultured with either viable or non-viable mycoplasmas. The supernatants of the macrophage culture with mycoplasmas, M. pneumoniae and Acholeplasma laidlawii, showed the potent cytotoxic activity to TNF-a-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Moreover, it was reported that TNF-a was induced by a various species of mycoplasmas by a protein kinase C-independent pathway (2,22,23,25). Our results were coincident with these.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that TNF-a was induced by a various species of mycoplasmas by a protein kinase C-independent pathway (2,22,23,25). Our results were coincident with these.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory substances include interleukin-8, tumor necrosis factor-, macrophage inflammatory peptide-1 [Hardy et al, 2001], intercellular adhesion molecule-1 [Krunkosky et al, 2007], and regulated upon activation, normal T cells expression and secreted [Dakhama et al, 2003], among others. Tumor necrosis factor-has been observed to be induced by M. pneumoniae in vitro from an early period of investigation [Arai et al, 1990;Kita et al, 1992]. This cytokine, along with interleukin-8, must play a pivotal role in eliciting vasculitic/thrombotic vascular occlusion.…”
Section: Direct Mechanisms Of Vasculitic/thrombotic Vascular Occlusionmentioning
confidence: 99%
“…The number of GAA repeats ranges from 10 to 16 (27). Genetic analysis of phenotypically switched clonal isolates, representing the ON or OFF expression state of the pMGA product from a number of pMGA genes in M. gallisepticum R, revealed that expressible pMGA genes always contained a (GAA) 12 motif. Different numbers of the GAA repeats were correlated with the OFF expression state of the pMGA (159).…”
Section: Random Genetic Control As a Major Strategy For Phenotypic Swmentioning
confidence: 99%
“…How does the (GAA) 12 motif function to initiate pMGA transcription? An intriguing model proposed by Glew (159) suggests that the (GAA) 12 motif serves as a linker or a spacer for two flanking binding sites necessary for the initiation of pMGA transcription. The first binding site, localized downstream of the (GAA) 12 motif, is a well-defined promoter site for RNA polymerase.…”
Section: Random Genetic Control As a Major Strategy For Phenotypic Swmentioning
confidence: 99%
See 1 more Smart Citation